Divine hunger: the cannibal war machine (2013)
This article identifies a deep historical and systemic relationship between the exercise of political power and a “Cannibal War Machine”, which appropriates forms and concepts belonging to the realms of witchcraft and the relation with the divine. It proposes that material and immaterial forms of violence have been the axis of all social exchanges in modernity, deploying death and suffering as a necessary artifact for progress, freedom and capitalist market through a logic that evokes the sacrifices to the gods and the sacred status of the liberal democratic order. From the conquest and colonization of the New World, the profits of plunder and extraction of the wealth of the Amerindian territory made the cannibal white-man (a stock figure in non- Western imagination) to unleash such a war machine that devours peoples and resources to feed the colonial State. In the contemporary world, the use of cutting-edge technologies swathes military actions with an aura of mystery, which mimics the imaginaries of magic and witchcraft, deliberately spreading a mystic that generates fear and social chaos, quite convenient to the military interests. After five centuries of intertwining of political power and violence, it would seem that the machine of war has not satiated itself and that it keeps claiming for more blood in the name of liberty and progress.